Hydrolysates from a Whey Protein Concentrate Are a Promising Functional Ingredient for Diabetes Control via DPP-IV Inhibition - Selene Isabel Alvarez-Chávez; Itzury Reyes-Ramírez; Luis Guillermo González-Olivares; Jesús Guadalupe Pérez-Flores; Elizabeth Contreras-López; Laura Berenice Olvera-Rosales; Laura García-Curiel; Emmanuel Pérez-Escalante (Biology and Life Sciences Forum)
The circular economy has been a strategy for diminishing waste and improving the use of natural resources and energy in different industrial sectors. The food industry is a manufacturing and service sector with few incorporations into sustainable development from the circular economy philosophy due to the absence of concrete or real scenarios to be carried out. The dairy industry has incorporated some strategies to mitigate the contamination, producing whey concentrate powders and their hydrolysates as alternatives. Thus, the work aimed to produce hydrolysates with antidiabetic functions from the hydrolysis with alcalase and flavourzyme of whey protein concentrate with 80% protein. Dispersions of whey powder were prepared in phosphate buffer at pH = 7.5 and hydrolyzed for 6 h at 60 °C and 130 rpm. The hydrolysates produced maintained an antidiabetic activity between 43% and 52% from dipeptidyl peptidase IV (DPP-IV) inhibition, with the alcalase enzyme slightly better. Thus, the enzymatic process tested on whey protein concentrate generated a promising ingredient for glycemic control.